Green biocatalysis - Patel, Ramesh N., 1942- (John Wiley & Sons, 2016)
"This book describes the enzyme-driven syntheses of industrially important compounds and chiral intermediates for chemicals and pharmaceuticals. The chapters describe recent technological advances in enzymatic and microbial transformations and are written by internationally renowned scientists and professors. The synthesis of industrially important molecules is described from the starting substrate to the final product and includes detailed mechanisms. This book addresses the use of various types of reactions catalyzed by microbial cells or enzymes derived from microbes in the production of industrially useful compounds and a variety of drugs. The production of chiral alcohols, amines, unnatural amino acids, esters, carboxylic acids, epoxides, hydroxylated compounds and drug metabolites as well as recent advances in enzyme catalyzed acylation, dehalogenation, esterification, oxidation-reduction, transamination, deamination, C-N, C-C, C-O bond formation, Baeyer-Villegar reaction and aldol as well as acyloin condensation reactions are covered. Cutting-edge topics such as directed evolution by gene shuffling and enzyme engineering to improve biocatalysts will be presented. Enzyme immobilization and reusability studies and enzymatic protection and deprotection are addressed as well"--